Bradyarrhythmias in Cardio-Oncology - Fonseca, Marta; Cheng, Evaline; Do, Duc; Haldar, Shouvik; Kutty, Shelby; Yang, Eric H.; Ghosh, Arjun K.; Guha, Avirup (South Asian Journal of Cancer, 2021)
The relationship between bradyarrhythmias and cancer therapies has not been well described but is increasingly recognized. There have been extensive advances in oncological pharmacotherapy, with several new classes of drugs available including targeted agents, immune checkpoint inhibitors and CAR T cell therapy. This increasing repertoire of available drugs has revolutionized overall prognosis and survival of cancer patients but the true extent of their cardiovascular toxicity is only beginning to be understood. Previous studies and published reviews have traditionally focused on conventional chemotherapies and in arrhythmias in general, particularly tachyarrhythmias. The number of patients with both cancer and cardiovascular problems is increasing globally and oncologists and cardiologists need to be adept at managing arrythmia based scenarios. Greater collaboration between the two specialties including studies with prospective data collection in Cardio-Oncology are much needed to fill in knowledge gaps in this arena. This case-based review summarizes current available evidence of cancer treatment-related bradyarrhythmia incidence (including its different subtypes), possible mechanisms and outcomes. Furthermore, we propose a stepwise surveillance and management protocol for patients with suspected bradyarrhythmia related to cancer treatment.
Keywords: bradyarrhythmia; cardio-oncology; checkpoint inhibitors; drug–drug interaction; radiation therapy